Contribution to the knowledge of the genus Vestalenula Rossetti & Martens, 1998 (Crustacea, Ostracoda, Darwinulidae), with the description of a new species, V. carinata n. sp., from the island of Florianópolis, Brazil - Pinto, Ricardo L.; Rocha, Carlos E. F.; Rossetti, Giampaolo; Martens, Koen (Zootaxa, 2013)
The genus Vestalenula is the most species rich in the putative ancient asexual ostracod Family Darwinulidae. Several new Recent species were described from various continents, mostly based on carapace shape and structure. These species were found in a variety of aquatic and (semi-) terrestrial habitats, including springs, streams, interstitial waters, leaf litter in for-ests and in splash zones of waterfalls. Here, we describe V. carinata n. sp. from moist leaf litter, collected from the Bra-zilian island of Florianópolis. The species belongs to the danielopoli-lineage within the genus because of its elongated internal tooth in the left valve and elongated external keel on the right valve. It can be distinguished from all other species in this group by its size, its L/H ratio and the relative length of the keel. The relationship of this new species to the enig-matic, putative marine species Semidarwinula terraenuxforma Choe, 1988, is discussed. An identification key to species of the genus is provided.